1995
DOI: 10.1002/marc.1995.030160907
|View full text |Cite
|
Sign up to set email alerts
|

A polarographic study of propene‐maleic anhydride copolymers

Abstract: The polarographic behaviour of hydrolyzed propene-maleic anhydride copolymers in the interval pH 2.0-1 1 .O has been investigated by differential pulse polarography in aqueous lithium chloride solution at 25 "C. In dependence on the pH-value, one, two or three signals, belonging to the acid groups in the copolymer, appear in the polarograms. Three apparent polarographic acid constants have been determined graphically from the changes in the halfwave potential of the separate peaks in correlation with pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It can be shown that the dissociation behaviour of the erythro-and threo-2,3-disubstituted succinic acid moieties formed, as is also known for low molecular weight 2,3-dialkyl succinic acids, [4] differs significantly, resulting in four different pK A -values for copolymers containing both the erythro-and the threo-form in the backbone. [5,6] This fact should also be of importance for the behaviour of MA copolymers as polyelectrolytes, complexing agents and in biochemical applications.…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that the dissociation behaviour of the erythro-and threo-2,3-disubstituted succinic acid moieties formed, as is also known for low molecular weight 2,3-dialkyl succinic acids, [4] differs significantly, resulting in four different pK A -values for copolymers containing both the erythro-and the threo-form in the backbone. [5,6] This fact should also be of importance for the behaviour of MA copolymers as polyelectrolytes, complexing agents and in biochemical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Polarographic measurements on the copolymer with propene evidenced three dissociation steps. 7 For some hydrolyzed alkene-maleic anhydride copolymers the different configurations of the succinic acid moiety can be assigned in the 13C-NMR spectra?-" The chemical shifts of the corresponding signals depend on the degree of neutralization adjusted. Combination of the results of 13C-NMR investigations and potentiometric titrations allows deeper insight into the dissociation behavior of the copolymers investigated.…”
Section: Introductionmentioning
confidence: 99%